Pengendalian Temperatur dan Kelembaban dalam Kumbung Jamur Tiram (Pleurotus sp) Secara Otomatis Berbasis Mikrokontroler - Sri Waluyo; Ribut Eko Wahyono; Budianto Lanya; Mareli Telaumbanua (agriTECH, 2018)
Oyster mushroom can grow properly at temperatures of 16–30 °C and relative humidity of 80–95%. Environment conditioning by spraying of water in mushroom house manually in the morning and evening as the temperature and humidity controling is less effective and highly bothersome. Using of technology can controlling temperature and humidity in a mushroom house automatically.  This research aims to design an automatic control system to control temperature and humidity in oyster mushroom house. Research is located at an altitude of 125 meters above sea level. Automatic control system with a setting point temperature of 25 – 30 °C and humidity of 80 – 95% was tested at mushroom house with dimensions of 4 × 2 × 2 m with a capacity of 600 baglog mushrooms.  The results show that the performance of daily temperature and humidity without control is respectively 24.10 to 35.19 °C and 64.28 to 99.90%. While the temperature and humidity with the control system are 25.10 to 30.09 °C and 80.84 to 99.90%, respectively.